Rancangan Aplikasi Rekam Medis Berbasis Web Dengan Scan Kode QR Pendaftaran Rawat Jalan Di RSU Suaka Insan Banjarmasin - Anisa Nuur Salman; Muhammad Rashif Anshari; Galih Persadha (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2023)
The rapid development of technology makes the dissemination of information can be done quickly so that it creates a big influence in society. One example of technological developments in the health sector that is starting to develop is the Hospital Management Information System (SIMRS). The use of information technology can be used to minimize the length of waiting time for outpatients and the provision of medical record documents and help reduce the workload of registration officers. One of the technologies that can be used is QR Code technology which is a link between patient treatment cards and the Hospital Management Information System (SIMRS). The research method uses research and development research with data collection based on interviews and observations. The results of this study are the design of the MNH (Medicine Index Card) with a QR code and the design of a web-based medical record application design by scanning the QR code at the Suaka Insan General Hospital Banjarmasin, namely the login page, dashboard, new patient registration menu, outpatient registration registration menu. old patients, and history of visits.